Victims’ profile by firearm related injuries in the municipality of the state of Rio de Janeiro - Graciele Oroski Paes; Simone Mendes Carvalho; Celso Alexandre Tavares Rodrigues; Joyce Maria dos Santos de Faria (O Mundo da Saúde)
Study of quantitative approach of descriptive/exploratory survey type with retrospective study between 2011 and 2012. The general objective was to investigate the victim’s profile related to firearm injury under the social aegis in a town of the Rio de Janeiro City, understanding that the urban violence crosses across several analysis dimensions among them: the social, the political and the cultural. The consultation sources came from occurrence forms taken by the twenty fifth battalion of the Rio de Janeiro state military police– known as 25th BPM, located in Cabo Frio (RJ) Municipality. There were found 305 notifications of victims of PAF in both of years researched, which 96% of the victims were identified by gender and age-group, and another 55% of the victims were between fifteen and thirty years old. The neighborhoods that occurred the largest amount of events were comprised for the most part from communities composed of low economic-social levels of individuals. The study contribution is anchored in orientation to preventive actions to the local population as well as to the elaboration of security public policies and awareness for the participation to combat and minimize the collaborative indexes of the local urban violence.